GENDER EQUALITY: WOMEN’S EMPOWERMENT - Yolqinovna, Asqaraliyeva Farzona (Antis Publisher, 2024)
General Background: Gender discrimination has been a pervasive issue throughout history, significantly hindering women and girls from reaching their full potential in various spheres of life. Specific Background: Despite progress towards gender equality, women continue to face systemic barriers in education, employment, and political participation, contributing to ongoing disparities and inequalities. Knowledge Gap: While existing literature addresses the historical roots and contemporary challenges of gender discrimination, there is a need for comprehensive strategies that promote gender equality and respect for all individuals, regardless of gender identity. Aims: This article aims to explore effective methods for building a society that values and respects all individuals, highlighting the importance of gender equality in fostering inclusive environments free from violence and discrimination. Results: The discussion reveals that addressing gender discrimination requires multi-faceted approaches, including policy reforms, educational initiatives, and community engagement, to dismantle barriers and promote equitable opportunities. Novelty: This article emphasizes the critical need for a holistic understanding of gender equality, integrating historical perspectives with contemporary strategies to advance social justice. Implications: The findings underscore the urgency of collective action to eliminate gender-based discrimination, ultimately contributing to a more just and equitable society where all women and girls can thrive free from inequality and violence.